Scanning Electron Microscopic Assessment of Stent Coating Integrity in Jailed Wire Technique for Bifurcation Treatment - Lijian Gao; Ce Zhang; Huanhuan Wang; Yiqun Zhang; Zhan Gao; Bo Xu; Jue Chen; Jinqing Yuan; Shubin Qiao; Jilin Chen (Journal of Interventional Cardiology)
Objectives. To assess the impact of different guidewires on stent coating integrity in jailed wire technique (JWT) for bifurcation treatment. Background. JWT is commonly adopted to protect side branch in provisional one-stent strategy for coronary bifurcation lesions. However, this technique may cause defects in stent coatings. The degree of coating damage caused by different types of jailed wires remains unknown. Methods. A fluid model with a bifurcation was established to mimic the condition in vivo. One-stent strategy was performed with three types of guidewire (nonpolymer-jacketed wire, intermediate polymer-jacketed wire, and full polymer-jacketed wire) tested for JWT. Scanning electron microscopy (SEM) was used to evaluate stent coating integrity and wire structure. The degrees of coating defects were recorded as no, slight, moderate, and severe defects. Results. A total of 27 samples were tested. Analyses of SEM images showed a significant difference in the degree of coating damage among the three types of wire after the procedure of JWT (P<0.001). Nonpolymer-jacketed wire could inevitably cause a severe defect in stent coatings, while full polymer-jacketed wire caused the least coating damages. Besides, there were varying degrees of coil deformation in nonpolymer-jacketed wires, while no surface damage or jacket shearing was observed in full polymer-jacketed wires. Conclusions. Although nonpolymer-jacketed wire has long been recommended for JWT, our bench-side study suggests that full polymer-jacketed wire may be a better choice. Further clinical studies are needed to confirm our findings.